The effect of giving potty training on the skills of defecating and urinating at toddler - Yosefina Nelista; Pembronia Nona Fembi; Teresia Elfi (Universitas Muhammadiyah Semarang, 2021)
Toddlers are an effective age to develop their various potentials which include physical, motor, cognitive, social-emotional development and language development. One of the child's developmental tasks is toileting skills or what are known as urinating and defecating skills. A skill that should be introduced early in toddlers to prevent enuresis is potty training. This study aims to analyze the effect of giving potty training on the independence of defecation and urination in toddlers. The type of research used is Quasy Experiment with one group pretest-posttest design research design. This study design only conducted an intervention in one group, without comparison. The population in this study were all children under five as many as 85 people. The sampling technique used purposive sampling so that the sample size in this study amounted to 30 people. Data analysis using Paired Samples Test. The results showed that there where there is an effect of giving potty training on defecation and urination skills in toddlers (p-value 0.000 <α 0.05). So it can be concluded that giving Potty Training can improve defecation and urination skills in toddlers.